The Tension Strength Experiment of Thread Connection Based on The Depth of Thread Penetration - Agus Santosa Sudjono; Lydia F. Tjong; Yohannes Yohannes (Civil Engineering Dimension, 2008)
Thread connection has been used for a long time. Presently, this kind of connection is the main connection in steel construction. This research aims to comprehend further the mechanism of the thread connection with respect to the depth of thread penetration. Tensile strength of thread connection was derived experimentally using two steel rods. The diameter of the first steel rod was Â¾ inch (18.5 mm) and threaded on one end by 16 threads per inch. The diameter of the second steel rod was 45 mm and functioned as nut. From the results of the experiment, it can be concluded that rod failure will happen if the depth of thread penetration is equal to or bigger than 90% of nut minor diameter. Meanwhile, thread failure will happen if the depth of thread penetration is less than 90% of nut minor diameter. It is also shown that the correlation between the number of thread and the maximum load which can be supported by the connection is not linear.